A bivalent virus-like particle based vaccine induces a balanced antibody response against both enterovirus 71 and norovirus in mice. Issue 43 (26th October 2015) - Wang, Xiaoli; Ku, Zhiqiang; Dai, Wenlong; Chen, Tan; Ye, Xiaohua; Zhang, Chao; Zhang, Yingyi; Liu, Qingwei; Jin, Xia; Huang, Zhong
Highlights A combination vaccine comprising EV71- and NoV GII.4-VLPs was formulated. The bivalent vaccine elicited a balanced antibody response toward both EV71 and GII.4. The bivalent vaccine-induced antibodies exhibited inhibitory effects on EV71 and NoV GII.4.